Video Pembelajaran Youtube untuk Media Pembelajaran Daring Mahasiswa - Junita Amalia; Regina Ayunita Tarigan (Yayasan Literasi Sains Indonesia, 2022)
This act of community dedication is aimed to provide video lessons of First Fundamental Mathematics/ First Calculus for the undergraduate students. The videos are free lesson source, accessible anytime and anywhere from Youtube. During the activity, there are a lot of positive responses from the students who are taking the same lessons as provided by the video materials. It can be concluded that the activity went very well and the result is as good as expected. This can be seen from the viewers’ enthusiasm who contribute in discussion on the comment section if they got stuck, appreciating the content, and also the high traffic. The fact that the most viewers are undergraduate students can be seen on Youtube analytic. As for the suggestion, if there is another team who wants to get the better result, it is strongly advised to promote and to share related information regarding the videos massively.